Pulmonary Hydatidosis in Children. A Case Presentation - Gladys Esther Escalante; Ivonne Espinosa Gómez; Yaquelin González Ricardo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
Hydatid disease or hydatidosis is a zoonotic parasitic disease, caused by the larval form of various species of tapeworms, common in dogs and other canines (wolves and jackals). Humans acquire it by ingesting eggs from the intestine or skin of their hosts. Few publications are reported in Cuba on these issues. We report a case of infection in an 8 year old girl admitted with the initial diagnosis of severe neumopathy and treated with various antimicrobial regimens without the expected success. It was found that she lived near parasitized dogs. With clinical, epidemiological, radiological and therapeutic diagnostic methods, hydatid disease was found. After anti-parasite treatment with albendazole for six months, favorable clinical evolution was confirmed the and radiological resolution of the images improved.